Discourse analysis of ESL undergraduate students’ patterns of interaction in an online peer feedback environment to develop writing performance - Baharudin, Muhammad Danial; Razali, Abu Bakar (Sciedu Press, 2022)
Academic writing is challenging for English as a Second Language (ESL) undergraduate students. One of the teaching strategies that language instructors use in teaching academic writing is by using peer feedback. However, in the ESL setting, many research has indicated mixed findings on the use of peer feedback. To contribute to the discussion, this qualitative study investigated the patterns of interaction between ESL students in an online peer feedback environment. The data were collected from six ESL undergraduate students through discourse analysis of their online peer feedback written interaction and content analysis of their essays. The findings revealed that two patterns of interaction emerged which include the expert/novice and dominant/passive pattern. However, there were none to small improvements among the students in terms of their writing performance. Although one of the patterns is collaborative (i.e., expert/novice), the quality and quantity of their feedback were lacking thus resulting in lower revisions and improvements made. The study recommends further research on the quality and quantity of peer feedback to understand better the role of online peer feedback in ESL students’ academic writing.